Organic Dyes based on Tetraaryl‐1, 4‐dihydropyrrolo‐[3, 2‐b]pyrroles for Photovoltaic and Photocatalysis Applications with the Suppressed Electron Recombination. Issue 68 (8th November 2018) - Wang, Jinfeng; Chai, Zhaofei; Liu, Siwei; Fang, Manman; Chang, Kai; Han, Mengmeng; Hong, Li; Han, Hongwei; Li, Qianqian; Li, Zhen
Abstract: A tetraaryl‐1, 4‐dihydropyrrolo‐[3, 2‐ b ]pyrroles (TAPP ) moiety with the combination of two pyrrole rings and four phenyl moieties demonstrated strong electron‐donating ability and nonplanar configuration simultaneously. Once incorporated into the organic dyes as a novel electron donor, it was beneficial for the enhancement of light‐harvesting ability and suppression of electron recombination in the photovoltaic and photocatalysis systems. With the linkage of tunable conjugated bridges and electron acceptor, the corresponding organic dyes exhibited improved photovoltaic performance in dye‐sensitized solar cells and facilitated photocatalytic hydrogen generation with a highest turnover number (TON) of 4337. Through the detailed investigation of relationship between molecular structures and photovoltaic/photocatalysis property, the connection and difference in molecular design for these two systems are well explained, with the aim to promote the application of dye‐sensitized technology in various fields. Abstract : TAPP dance : With the incorporation of tetraaryl‐1, 4‐dihydropyrrolo‐[3, 2‐ b ]pyrroles (TAPP) derivatives into organic dyes as novel electron donors, the optimized photovoltaic and photocatalysis performance is achieved by the efficient suppression of electron recombination in different conditions.